Death Receptor 3 Signaling Controls the Balance between Regulatory and Effector Lymphocytes in SAMP1/YitFc Mice with Crohn’s Disease-Like Ileitis - Li, Zhaodong (Front Immunol, 2018)
Death receptor 3 (DR3), a member of the tumor necrosis factor receptor (TNFR) superfamily, has been implicated in regulating T-helper type-1 (T(H)1), type-2 (T(H)2), and type-17 (T(H)17) responses as well as regulatory T cell (T(reg)) and innate lymphoid cell (ILC) functions during immune-mediated diseases. However, the role of DR3 in controlling lymphocyte functions in inflammatory bowel disease (IBD) is not fully understood. Recent studies have shown that activation of DR3 signaling modulates T(reg) expansion suggesting that stimulation of DR3 represents a potential therapeutic target in human inflammatory diseases, including Crohn’s disease (CD). In this study, we tested a specific DR3 agonistic antibody (4C12) in SAMP1/YitFc (SAMP) mice with CD-like ileitis. Interestingly, treatment with 4C12 prior to disease manifestation markedly worsened the severity of ileitis in SAMP mice despite an increase in FoxP3(+) lymphocytes in mesenteric lymph node (MLN) and small-intestinal lamina propria (LP) cells. Disease exacerbation was dominated by overproduction of both T(H)1 and T(H)2 cytokines and associated with expansion of dysfunctional CD25(−)FoxP3(+) and ILC group 1 (ILC1) cells. These effects were accompanied by a reduction in CD25(+)FoxP3(+) and ILC group 3 (ILC3) cells. By comparison, genetic deletion of DR3 effectively reversed the inflammatory phenotype in SAMP mice by promoting the expansion of CD25(+)FoxP3(+) over CD25(−)FoxP3(+) cells and the production of IL-10 protein. Collectively, our data demonstrate that DR3 signaling modulates a multicellular network, encompassing T(regs), T effectors, and ILCs, governing disease development and progression in SAMP mice with CD-like ileitis. Manipulating DR3 signaling toward the restoration of the balance between protective and inflammatory lymphocytes may represent a novel and targeted therapeutic modality for patients with CD.